Reflection on the online learning of Pancasila and Citizenship in an international class program - Elisabeth Rukmini; Pedy Artsanti; Arya Susila Nugraha (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
The main problem of the Pancasila and Citizenship courses is the substance problem which is cognitive domains, and the problem of learning approaches. This research results from active collaboration between universities online with the Pancasila & Citizenship learning design for international class students of FTI UII. This research aims to explore the results of online learning Pancasila and Citizenship from student reflections. This goal is to be achieved by analyzing qualitative data on student reflections and analyzing the results of student evaluations of the five-step learning program "To Live Pancasila in Our (Global) Citizenship". Qualitative analysis was carried out through content analysis, while the evaluation results were descriptive responses. The reflections of 24 student respondents were gathered into the categories of Pancasila, Citizenship, Meaningful, and Reflect on the Future. The results of the analysis show that the Pancasila & Citizenship course has a novelty in meaning, learning content, and future reflection. The content of learning is about law/regulation, daily life, religious aspects, and tolerance. Furthermore, tolerance breeds respect/appreciation/appreciation. Learning content is conveyed through virtual interactions towards meaningful learning. Future reflection here is related to the learner's awareness or choice manifested in participation. The learning approach, which is blended learning and flipped material, allows students to understand the material and deposit it in reflection